Analysis CID Volcanic Earthquake in The Sunda Strait Due to The Eruption of Anak Gunung Krakatau - Atika Sari; Mokhamad Nur Cahyadi (Direktorat Riset dan Pengabdian Masyarakat (DRPM), ITS, 2019)
In earthquakes occur three types of waves, namely acoustic waves with vertical directions from the epicenter to the ionosphere F, gravity waves are waves generated from the tsunami, and the resulting Rayleigh waves move away from the epicenter. These waves create disturbances in the ionosphere, namely at electron density. The electron density in the ionosphere layer is called Total Electron Content (TEC). This phenomenon is detected as CID (Coseismic Ionosphere Disturbance), ie TEC fluctuations that occur ` 10 minutes after the earthquake. Earthquakes that are used as case studies are earthquakes that occur in the volcanic earthquake in the Sunda strait due to volcanic eruptions of krakatu children resulting in tsunamis on the Sunda Strait on December 22, 2018 (doy 356) with magnitude 5 SR at 13.55 UTC. In this study using the data of GNS (Global Navigation Satellite System) BIG CORS (Continuous Operating Reference Station) (Geospatial Information Agency uses CRKS, CPSR and CGON stations. The results of this study note that GPS number 3 detects TEC fluctuations after a volcanic earthquake. The biggest fluctuation worth 0.422 TECU which is at 9 minutes after the volcanic earthquake of the child of Mount Krakatau.